Tìm x:
5x(1-2x) -3x(x+18)=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a. (3x - 1).(2x + 7) - (x + 1).(6x - 5) = 16
<=> 6x^2 + 19x - 7 - (6x^2 + x - 5) = 16
<=> 18x - 2 = 16
<=> 18x = 18
<=> x = 1
b. (10x + 9).x - (5x - 1).(2x + 3) = 8
<=> 10x^2 + 9x - (10x^2 + 13x - 3) = 8
<=> -4x + 3 = 8
<=> -4x = 5
<=> x = -5/4
c. (3x - 5).(7 - 5x) + (5x + 2).(3x - 2) - 2 = 0
<=> -15x^2 + 46x - 35 + 15x^2 - 4x - 4 - 2 = 0
<=> 42x - 41 = 0
<=> x = 41/42
Lời giải:
a.
PT $\Leftrightarrow 3x^2+\frac{x}{2}-3x^2+3x+2=0$
$\Leftrightarrow \frac{7}{2}x+2=0$
$\Leftrightarrow \frac{7}{2}x=-2$
$\Leftrightarrow x=-2: \frac{7}{2}=\frac{-4}{7}$
b.
PT $\Leftrightarrow 5x^2-3-5x^2-6x=0$
$\Leftrightarrow -3-6x=0$
$\Leftrightarrow 6x=-3$
$\Leftrightarrow x=\frac{-3}{6}=\frac{-1}{2}$
20) -5-(x + 3) = 2 - 5x ⇔ -5 - x - 3 = 2 -5x ⇔ 4x = 10 ⇔ x = \(\frac{5}{2}\)
Vậy...
a: a(x)=x^3+3x^2+5x-18
b(x)=-x^3-3x^2+2x-2
b: m(x)=a(x)+b(x)
=x^3+3x^2+5x-18-x^3-3x^2+2x-2
=7x-20
c: m(x)=0
=>7x-20=0
=>x=20/7
+) (5x-1). (2x+3)-3. (3x-1)=0
10x^2+15x-2x-3 - 9x+3=0
10x^2 +8x=0
2x(5x+4)=0
=> x=0 hoặc x= -4/5
+) x^3 (2x-3)-x^2 (4x^2-6x+2)=0
2x^4 -3x^3 -4x^4 + 6x^3 - 2x^2=0
-2x^4 + 3x^3-2x^2=0
x^2(-2x^2+x-2)=0
-2x^2(x-1)^2=0
=> x=0 hoặc x=1
+) x (x-1)-x^2+2x=5
x^2 -x -x^2+2x=5
x=5
+) 8 (x-2)-2 (3x-4)=25
8x - 16-6x+8=25
2x=33
x=33/2
\(5x\left(1-2x\right)-3x\left(x+18\right)=0\)
\(\Leftrightarrow5x-10x^2-3x^2-54x\)
\(\Leftrightarrow-13x^2-49x=0\)
\(\Leftrightarrow x\left(-13x-49\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\-13x=49\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-\dfrac{49}{13}\end{matrix}\right.\)
Vậy ..
\(5x\left(1-2x\right)-3x\left(x+18\right)=0\)
=>\(5x-10x^2-3x^2-54x=0\)
=> \(-49x-13x^2=0\)
=> \(x\left(-49-13x\right)=0\)
=> \(\left[{}\begin{matrix}x=0\\-49-13x=0\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=0\\-49=13x\end{matrix}\right.\)
=> \(\left[{}\begin{matrix}x=0\\x=\dfrac{-49}{13}\end{matrix}\right.\)
Vậy \(x\in\left\{\dfrac{-49}{13};0\right\}\)
\(5x\left(1-2x\right)-3x\left(x+18\right)=0\)
=> \(5x-10x^2-3x^2-54x=0\)
=> \(-13x^2-49x=0\)
=> \(-x\left(13x+49\right)=0\)
=> \(-x=0\) hoặc : \(13x+49=0\)
=> \(x=0\) hoặc: \(13x=-49\Rightarrow x=\frac{-49}{13}\)
\(5x\left(1-2x\right)-3x\left(x+18\right)=0\)
=> \(5x-10x^2-3x^2-54x=0\)
=> \(-49x-13x^2=0\)
=> \(-x\left(49+13x\right)=0\)
=> \(-x=0\) hoặc \(49+13x=0\)
=> \(x=0\) hoặc \(13x=-49\Rightarrow x=-\frac{49}{13}\)
\(5x\left(1-2x\right)-3x\left(x+18\right)=0\)
\(5x-10x^2-3x^2-54x=0\)
\(-13x^2-49x=0\)
\(\left(-13x-49\right)x=0\)
TH1: x=0
TH2: -13x-49=0
-13x = 49
x = \(-\frac{49}{13}\)
Vậy x=0 và x = \(-\frac{49}{13}\)
5-10x=3x+54
10x=3x+49
7x=49
Vậy x=7